Phytochemical compound determination of Entada rheedei Spreng and its antifungal activity on selected soilborne fungal phytopathogens - Che Mohd Ramli, Neni Kartini (2013)
This study presents the potential use of natural products from Entada rheedei Spreng. as biofungicide and their antifungal activity against five common soilborne fungal pathogens. The dried leaves, stems and seeds of E. rheedei were extracted by sequential extraction using petroleum ether, chloroform, methanol and water. Among the four solvents used, methanol (MeOH) was proven to be the best extracting solvent by giving the highest quantity of crude extract yielding 7.74g (3.87%) of stems crude extract, 1.861g (0.93%) of leaves crude extract and 26.6g (13.3%) of seed crude extract. The gained crude extracts were then screened via in vitro assays for their antifungal activity, using well diffusion method, against five selected soilborne fungal pathogens Rhizoctonia solani, Fusarium commune, Fusarium oxysporum f.sp. cubense (FOC), Pythium ultimum and Phytophthora palmivora. The petroleum ether and chloroform extracts of stems, seeds and leaves of E. rheedei failed to inhibit the growth of all tested soilborne fungal phytopathogens. The best inhibitory effect was elicited by the stems and seeds crude methanol extracts against Fusarium commune (51.4% and 50% radial growth inhibition respectively), while crude water and methanol extracts of seed against FOC showed the least significant effect (15% radial growth inhibition). Nevertheless, seed crude methanol and water extracts gave an impressive inhibitory on radial growth of F. commune with 50% and 36.7% inhibition respectively. Moreover, stem crude methanol and water extracts also showed moderately significant inhibitory against FOC (45% and 42.5% inhibitory respectively). The results also showed that all the stem and seed methanol and water crude extracts failed to inhibit the growth of R. solani, P. ultimum and P. palmivora. The Effective Inhibitory Concentration (EIC) of stem and seed crude methanol and water were determined at 100mg/mL. The phytochemical analysis of the active crude extracts revealed the presence of tannins, saponins, glycosides, triterpenoid, and alkaloid which only present in seed. Light and scanning electron microscopic observation on the effect of active crude extracts on spore germination and hyphal growth of F. commune and FOC illustrated that the spore and hyphae were collapsed and lysed; cell wall were degraded and shrank; while the spore (macroconidia) failed to germinate. The active crude extracts were further purified through Vacuum Liquid Chromatography (VLC) fractionation and resulted in the total of 22 fractions with 11 fractions for each stem and seed methanolic extracts. The obtained fractions were then screened for the antifungal activity against the selected soilborne fungal pathogens. Results showed some improvement on antifungal activity of the stem and seed methanolic fractions. The fraction eluted with chloroform: methanol in the ratio of 6:5 (F5) and 5:5 (F6) of stem methanol proved to be the most active fractions against F. commune (56.8% and 45.9% growth inhibition) and FOC (48.7% and 43.6% growth inhibition). All fractions of stem and seed methanolic extracts showed some improvement in their antifungal activity against R. solani and P. palmivora, which were not shown previously by any of their parent crude extracts. The TLC phytochemical analysis showed the presence of saponin and tannin in the fractions F4, F5, F6 and F7 of stem and seed methanolic extracts. The determination of major active compound in the active fractions via High Performance Liquid Chromatography (HPLC) analysis, to confirm the major constituent contained in the active fractions, showed that the active fractions (F4-F7) of stem and seed methanolic extracts of E. rheedei contain saponin as major active compound.